Antimicrobial potential of 70% ethanol extract of Acalypha siamensis leaf against Escherichia coli, Streptococcus mutans, and Candida albicans - Putri, Oktavina Kartika; Rohmatika, Arini; Kutsiyah; Pratikasari, Yunita Wahyu (JSMARTech: Journal of Smart Bioprospecting and Technology, 2026)
Acalypha siamensis is a promising Indonesian plant. However, not many people know about its diverse benefits, particularly its antimicrobial properties against various pathogenic microbes. This study aims to evaluate the antimicrobial potential of 70% ethanol extract of A. siamensis leaf against Escherichia coli, Streptococcus mutans, and Candida albicans. The extraction method used in this study was remaceration. Identification of active compounds was carried out using qualitative phytochemical tests with specific reagents. Antimicrobial activity was determined using the well diffusion method. The extraction process yielded a percentage of 26.1414 ± 0.7797%. Qualitative phytochemical tests revealed the presence of bioactive compounds such as phenolics, flavonoids, alkaloids, saponins, and tannins. Antimicrobial activity was assessed and showed inhibition zones of 12.723 ± 1.339 mm against E. coli, 7.086 ± 0.782 mm against S. mutans, and 4.188 ± 1.304 mm against C. albicans. These results indicate that the 70% ethanol extract of A. siamensis leaf exhibits notable antimicrobial activity, particularly against E. coli, and has potential as a natural antimicrobial agent. Keywords: Acalypha siamensis, antimicrobial activity, Candida albicans, Escherichia coli, Streptococcus mutans